Proceedings of First International Conference on Information and Communication Technology for Intelligent Systems: Volume 1 - Satapathy, Suresh Chandra; Das, Swagatam; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This volume contains 59 papers presented at ICTIS 2015: International Conference on Information and Communication Technology for Intelligent Systems. The conference was held during 28th and 29th November, 2015, Ahmedabad, India and organized communally by Venus International College of Technology, Association of Computer Machinery, Ahmedabad Chapter and Supported by Computer Society of India Division IV - Communication and Division V - Education and Research. This volume contains papers mainly focused on ICT for Computation, Algorithms and Data Analytics etc.
Intelligent Information Retrieval And Business Intelligence -- Intelligent Web Mining And Knowledge Discovery Systems -- Applications for Intelligent Systems -- Applications of ICT in Rural and Urban Areas -- ICT for Information Sciences.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence